The Board of Directors Corporate Governance and the Effect on Firm Value - Croci, Ettore (Springer International Publishing, 2018)
Boards of directors are a central feature of any corporate governance regime. The role of directors and how they affect firm value and policies is examined in depth in academic literature. However, it is easy to get both lost and overwhelmed when searching through the literature review that investigates several characteristics, often one at the time. This book provides a careful and concise look at corporate finance literature, specifically with regard to the board of directors, summarizing the main findings and reconciling them. This book documents the pros and cons associated with the various attributes of the board and the directors as found in the current literature and provides sections geared specifically to practitioners in this space, as well, allowing for a better and more comprehensive description of this important corporate governance mechanism. The resulting book aims to facilitate the interpretation of changes in corporate governance through the lens of the recent academic literature.